2021
DOI: 10.1029/2020jd034428
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Climatic Effects of Irrigation Over China by Using the WRF‐Noah Model System With Mosaic Approach

Abstract: Investigation on the climatic effects of irrigation is of great significance to fully understand the impact of water management on the Earth's environment and hydrological cycle. To comprehensively explore the effects of irrigation across different climatic regions over China, we propose a novel combined irrigation scheme (including dynamic and fixed irrigation schemes) into the Weather Research and Forecasting (WRF)‐Noah‐mosaic model. Two experiments (with and without irrigation) are designed to simulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 94 publications
(208 reference statements)
0
21
0
Order By: Relevance
“…For example, Zhong et al (2017) highlighted that urban heat islands in the Yangtze River Delta urban cluster can increase extreme summer rainfall through enhanced afternoon convergence and updrafts. Liu et al (2021a) revealed that the cooling and wetting effects of irrigation exerted opposite impacts on convective precipitation over China. To better assess the climate effects of realistic LUCCs, the effects of vegetation changes, urbanization and land management changes (e.g., irrigation) on regional climate need to be considered and quantified simultaneously in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhong et al (2017) highlighted that urban heat islands in the Yangtze River Delta urban cluster can increase extreme summer rainfall through enhanced afternoon convergence and updrafts. Liu et al (2021a) revealed that the cooling and wetting effects of irrigation exerted opposite impacts on convective precipitation over China. To better assess the climate effects of realistic LUCCs, the effects of vegetation changes, urbanization and land management changes (e.g., irrigation) on regional climate need to be considered and quantified simultaneously in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset further includes spatial information about multi-cropping agricultural land as well as irrigation calendars. MIRCA2000 has been used in multiple studies, e.g., Leng et al (2017), Cheng et al (2021), andLiu et al (2021). For the continental United States, two other datasets of irrigated areas are available at higher resolution, namely (i) Ozdogan and Gutman (2008) at ∼500 meters resolution and (ii) the Irrigated Agriculture Dataset (MIrAD-US) developed by Pervez and Brown (2010) and Brown and Pervez (2014) at 250 meters.…”
Section: Spatial Dimensionmentioning
confidence: 99%
“…The latter approach is expressed as the number of consecutive hours h I , and is used to localize the irrigation procedure in time (e.g., Leng et al, 2013;Valmassoi et al, 2020a). Examples of different start hours and length are 06 local and 4 h (e.g., Ozdogan et al, 2009;Leng et al, 2013;Yang et al, 2016), 08 (Liu et al, 2021) or 09 (Evans and Zaitchik, 2008;Wu et al, 2018) local time and for 2 h and 30 min, respectively, or a sensitivity to these parameters by Valmassoi et al (2020a). The irrigation duration period is usually employed to equally partition the calculated water over all the consecutive hours, transforming the quantity to a rate (mm s −1 ), for example.…”
Section: Temporal Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change influences grain production as the atmospheric conditions and water supply alter, which makes the climatic research regarding 3HP greatly significant. Understanding the specific environmental impact of urbanization and irrigation is of great significance to fully understanding the regional climate response to the land use policy and water management (G. Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%